2022
DOI: 10.3390/f13020355
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Resources on the Adaptability of State Forest Companies. Some Evidence from the State Forests National Forest Holding

Abstract: Structural, economic, and climate changes human activity and the growing complexity of the business environment significantly affect the forestry sector, which faces the need to adapt to the dynamically changing environment by strategic development of appropriate resources and skills. In this paper, we attempted to take on the managerial lens of dynamic capabilities, i.e., the abilities to adapt to the changes in the business environment to analyze whether the forestry sector is able to strategically develop r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…Huarng et al indicated that knowledge is the source of innovation and new knowledge is an antecedent of innovation [82]. Dyduch et al emphasised the role of dynamic capabilities, value creation and value capture [83], while Cyfert et al highlighted the role of the developing dynamic capabilities process [84,85]. In turn, Rajapathirana and Hui indicated the following determinants of innovation capability: organizational culture, use of knowledge from different sources, involvement of workers and customers, etc.…”
Section: Organisational Characteristicsmentioning
confidence: 99%
“…Huarng et al indicated that knowledge is the source of innovation and new knowledge is an antecedent of innovation [82]. Dyduch et al emphasised the role of dynamic capabilities, value creation and value capture [83], while Cyfert et al highlighted the role of the developing dynamic capabilities process [84,85]. In turn, Rajapathirana and Hui indicated the following determinants of innovation capability: organizational culture, use of knowledge from different sources, involvement of workers and customers, etc.…”
Section: Organisational Characteristicsmentioning
confidence: 99%
“…At the same time, water resources, water ecology, water environment and water disasters are frequent (Yuan & Zheng, 2022) [ 47 ], and water resources play an extremely important role in human production and life, so it is important to monitor and examine water resources. Today, the threat of severe weather phenomena such as climate change impacts, fires, insect and plant invasions, diseases, storms, floods, temperature changes or droughts, and increased economic and human activities have put forests around the world under a great deal of pressure (Cyfert & Dyduch, 2022) [ 48 ], and forest resources have always played a pivotal role in advancing the course of human civilization, and their It is important to protect them. Energy as a raw material for power has always been an essential element in driving human civilization (Hoho et al, 2015) [ 49 ].…”
Section: Constructing An Ecological Civilization Evaluation Index Sys...mentioning
confidence: 99%
“…Uji KMO (Kaiser-Meyer-Olkin) merupakan metode yang digunakan untuk menguji sejauh mana korelasi parsial antar variabel dapat dijelaskan oleh faktor-faktor yang ada, yang mana memberikan informasi tentang kekuatan hubungan antar variabel (Antony & Visweswara Rao, 2007). Nilai KMO yang mendekati 1,0 dianggap sebagai kondisi ideal, sedangkan nilai di bawah 0,5 dianggap tidak layak (Cyfert et al, 2022;Tehupeiory et al, 2023).…”
Section: Hasil Dan Pembahasanunclassified